Phenotypic, chemical and functional characterization of cyclic nucleotide phosphodiesterase 4 (PDE4) as a potential anthelmintic drug target. - Thavy Long; Liliana Rojo-Arreola; Da Shi; Nelly El-Sakkary; Kurt Jarnagin; Fernando Rock; Maliwan Meewan; Alberto A Rascón; Lin Lin; Katherine A Cunningham; George A Lemieux; Larissa Podust; et al. (Public Library of Science (PLoS), 2017)
Reliance on just one drug to treat the prevalent tropical disease, schistosomiasis, spurs the search for new drugs and drug targets. Inhibitors of human cyclic nucleotide phosphodiesterases (huPDEs), including PDE4, are under development as novel drugs to treat a range of chronic indications including asthma, chronic obstructive pulmonary disease and Alzheimer's disease. One class of huPDE4 inhibitors that has yielded marketed drugs is the benzoxaboroles (Anacor Pharmaceuticals).A phenotypic screen involving Schistosoma mansoni and 1,085 benzoxaboroles identified a subset of huPDE4 inhibitors that induced parasite hypermotility and degeneration. To uncover the putative schistosome PDE4 target, we characterized four PDE4 sequences (SmPDE4A-D) in the parasite's genome and transcriptome, and cloned and recombinantly expressed the catalytic domain of SmPDE4A. Among a set of benzoxaboroles and catechol inhibitors that differentially inhibit huPDE4, a relationship between the inhibition of SmPDE4A, and parasite hypermotility and degeneration, was measured. To validate SmPDE4A as the benzoxaborole molecular target, we first generated Caenorhabditis elegans lines that express a cDNA for smpde4a on a pde4(ce268) mutant (hypermotile) background: the smpde4a transgene restored mutant worm motility to that of the wild type. We then showed that benzoxaborole inhibitors of SmPDE4A that induce hypermotility in the schistosome also elicit a hypermotile response in the C. elegans lines that express the smpde4a transgene, thereby confirming SmPDE4A as the relevant target.The orthogonal chemical, biological and genetic strategies employed identify SmPDE4A's contribution to parasite motility and degeneration, and its potential as a drug target. Transgenic C. elegans is highlighted as a potential screening tool to optimize small molecule chemistries to flatworm molecular drug targets.